2021
DOI: 10.1038/s41598-021-90817-z
|View full text |Cite
|
Sign up to set email alerts
|

A binge high sucrose diet provokes systemic and cerebral inflammation in rats without inducing obesity

Abstract: While the dire cardiometabolic consequences of the hypercaloric modern ‘Western’ diet are well known, there is not much information on the health impact of a high sucrose diet not inducing weight gain. Here, we tested the hypothesis that rats reared with intermittent binge access to sucrose in addition to normal chow would develop an inflammatory response in brain. To test this hypothesis, we undertook serial PET/MRI scans with the TSPO ligand [18F]DPA714 in a group of (n=9) rats at baseline and again after vo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Research showed that consumption of 11% sucrose solution for 4 weeks did not increase neuroinflammation in rats [ 74 ], while a prolonged high sucrose intake (5% sucrose solution) for 12 weeks provoked systemic and neuroinflammation in rats [ 75 ]. In addition, Hsu’s study showed that high sucrose intake for 4 weeks moderately impaired hippocampal-dependent spatial learning and memory in adolescent rats [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research showed that consumption of 11% sucrose solution for 4 weeks did not increase neuroinflammation in rats [ 74 ], while a prolonged high sucrose intake (5% sucrose solution) for 12 weeks provoked systemic and neuroinflammation in rats [ 75 ]. In addition, Hsu’s study showed that high sucrose intake for 4 weeks moderately impaired hippocampal-dependent spatial learning and memory in adolescent rats [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…To calculate IBA1 + cell body size, maximum intensity projections (MIPs) were opened in Fiji v1.5 and the free drawing tool was used to measure the area of positive cells with a visible nucleus (20 cells per animal). For microglial arborisation, images were analysed as previously described ( Patkar et al, 2021b ).…”
Section: Methodsmentioning
confidence: 99%
“…This idea was strengthened when studies using the type 1 diabetes model, which does not include an HFD, also showed increased microglial hypertrophy, astrocytic activation and proliferation, and increased proinflammatory gene expression in the hypothalamus [77,85,86]. Further, a recent study showed an increase in the microglial density in the hypothalamus of the binge sucrose rats [87]. Apart from the different hyperglycemic mice models, the direct administration of glucose into the mouse third ventricle has shown a significant increase in the nuclear factor kappa light chain enhancer of activated B cells (NF-κB) activity in the hypothalamus [20].…”
Section: B Hyperglycemiamentioning
confidence: 99%